Early Locomotor Training in Tetraplegic Post-Surgical Dogs with Cervical Intervertebral Disc Disease - Débora Gouveia; Carla Carvalho; Ana Cardoso; Óscar Gamboa; António Almeida; António Ferreira; Ângela Martins (Animals, 2022)
Locomotor training (LT) is task-specific repetitive training, with sensorimotor stimulation and intensive exercises that promote neuromuscular reorganization. This study aimed to observe if LT could be initiated safely in the first 3–15 days after surgery in tetraplegic C1–C5 IVDD—Hansen type I dogs. This prospective blinded clinical study was conducted at two rehabilitation centers in Portugal, with 114 grade 1 (MFS/OFS) dogs, divided by the presence of spinal hyperesthesia into the SHG (spinal hyperesthesia group) (n = 74) and the NSHG (non-spinal hyperesthesia group) (n = 40), evaluated in each time point for two weeks according to a neurorehabilitation checklist by three observers for inter-agreement relation. LT was safely applied with 62.3% of the OFS ≥ 11 within 15 days and of these, 32.4% achieved a OFS ≥ 13. There were no new cases of hyperesthesia in the NSHG and from the SHG all recovered. Comparing groups, a significant difference was observed in their ability to achieve ambulatory status (p < 0.001), between the presence of hyperesthesia and days until ambulation (p < 0.006) and in each time point (p < 0.001; R2 = 0.809). Early LT may be a safe treatment to be applied in the first 3 days on these dogs and spinal hyperesthesia should be important to the rehabilitation team. This study should be continued.